UTHM Losthub – Mobile Application for Lost and Found Items in UTHM - Rahim, Razlan; Arbain, Siti Hajar (Applied Information Technology And Computer Science, 2026)
This paper presents the design and development of UTHM LostHub, a mobile application aimed at addressing the inefficiencies in managing lost and found items at Universiti Tun Hussein Onn Malaysia (UTHM). The existing methods such as notice boards and social media were found to be unstructured and unreliable. UTHM LostHub was developed as a centralized, user-friendly platform using Android Studio and Firebase, enabling students and staff to report, search, and manage lost and found items efficiently. The project adopted a prototyping model, allowing iterative development and integration of user feedback. Key features include secure authentication via institutional email, advanced item filtering, and direct communication between users. Comparative analysis with similar systems demonstrated the advantages of LostHub in terms of usability and functionality. The application underwent extensive functional and user acceptance testing (UAT), with results showing high user satisfaction and positive feedback on its interface and core features. While the system performs well, minor limitations were identified, including the absence of a password recovery feature and occasional performance issues. Future improvements will focus on optimizing system performance and enhancing accessibility. The UTHM LostHub app stands as a practical digital solution for improving campus-wide lost and found item management.